Home dental service in child with chromosome 9 trisomy – mosaic type: case report (Research, Society and Development, 2022)
The Chromosome 9, Trisomy mosaic (T9M) is a rare multisystemic disorder with broad clinical phenotype, vast individual variability, increased risk of prenatal and perinatal problems, and associated with advanced parental age. The main discoveries are craniofacial dysmorphisms, multiple organ malformations, and neurological and psychomotor development delay. The goal is reporting general and buccal characteristics, as well as the home care dental treatment in a child with T9M. Child at 2 years and 6 months old, female, with home dental service during the pandemic, because the mother reported that the child was restless. The patient uses nasogastric tube and had recent introduction of liquid food, with anti-reflux valve. During the clinical examination, we diagnosed generalized gingivitis, presence of reddish area on palate and rash hematoma in the 54. The orientation given to mother and helpers was to make hygiene with fluoridated toothpaste, individualizing the technics: single tufted toothbrush for molars, flossing with teeth floss rod, using tongue scraper, and using mouth opener made out of popsicle sticks. For Candidiasis treatment, a topical antifungal (VASA solution) was used for three weeks, which caused wound remission. The dental home service for treating T9M requires humanized perspective and early childhood care, which improves the quality of life.